Management of The Impact of Sharia Fintech Implementation on Financial Inclusion of Marginalized Communities - Syafiul Umam; Muhammad Syafi'i Budi Santoso; Abdul Wakhid; Ahmad Syahni; Dimyati Dimyati (LPPM STIES BABUSSALAM, 2026)
This study examines the impact of Sharia fintech implementation on the financial inclusion of marginalized communities. The rapid development of financial technology based on Islamic principles has created new opportunities for expanding access to financial services among underserved populations, particularly those facing geographical, economic, and social barriers. The objective of this study is to analyze the role of Sharia fintech in improving access to financial services, promoting economic empowerment, and supporting sustainable financial inclusion. This research employs a qualitative descriptive approach through a comprehensive review of relevant literature, regulatory frameworks, and empirical findings related to Islamic financial technology and financial inclusion. The findings indicate that Sharia fintech contributes significantly to increasing access to financing, savings, payment systems, and financial literacy among marginalized communities. Furthermore, the principles of transparency, fairness, and prohibition of usury embedded in Sharia fintech enhance public trust and encourage broader participation in the formal financial sector. However, challenges such as limited digital literacy, inadequate technological infrastructure, regulatory constraints, and low public awareness remain significant barriers to maximizing its impact. The study concludes that strengthening regulatory support, improving digital literacy, and enhancing collaboration among stakeholders are essential to optimizing the contribution of Sharia fintech to inclusive and sustainable economic development